2017
DOI: 10.1002/marc.201700486
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Docking and Undocking Processes Addressing Selectively the Outside and Inside of Polymersomes

Abstract: Increasing complexity and diversity of polymersomes and their compartments is a key issue for mimicking cellular functions and protocells. Thus, new challenges arise in terms of achieving tunable membrane permeability and combining it with control over the membrane diffusion process, and thus enabling a localized and dynamic control of functionality and docking possibilities within or on the surface of polymeric compartments. This study reports the concept of polymersomes with pH-tunable membrane permeability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…42,60,63 Once the Psomes are obtained, they are crosslinked for 3 min of UV irradiation, if not otherwise mentioned, to obtain robust and pH-stable polymeric vesicles (Figure 1 and Table 1). 42,43,60,63,64 In situ and post loading method was used to fabricate Avidin-Psomes. In situ loading describes the encapsulation of cargo during the formation of Psomes, while post loading implies the encapsulation and/or interaction of cargo by/with Psomes after their formation (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42,60,63 Once the Psomes are obtained, they are crosslinked for 3 min of UV irradiation, if not otherwise mentioned, to obtain robust and pH-stable polymeric vesicles (Figure 1 and Table 1). 42,43,60,63,64 In situ and post loading method was used to fabricate Avidin-Psomes. In situ loading describes the encapsulation of cargo during the formation of Psomes, while post loading implies the encapsulation and/or interaction of cargo by/with Psomes after their formation (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Known from a previous study that glycodendrimer b7 is suited to cross the membrane. 43 Generally, the post loading approach for Avidin-Psomes leads to a successful loading of all kinds of biotinylated (macro)molecules. Thus, this study emphasizes an alternative to the in situ loading process of Psomes.…”
Section: Aap High Fluorencencementioning
confidence: 99%
“…One of the cross-linked polymersomes, which have been studied very intensively over the last 10 years, are the photo-cross-linked and pH sensitive ones from Voit et al first reported in 2011 [59]. We will now focus on this polymer and the application of the corresponding polymersomes as functional nanoreactors as single compartment and novel contribution in the field of multicompartments [9,17,[60][61][62][63][64][65][66][67].…”
Section: Photo-cross-linked and Ph-sensitive Polymersomesmentioning
confidence: 99%
“…Common linker groups for covalent binding approaches are amine moieties, carboxyl groups, azido, or alkyne groups to utilize esterification and click chemistries on the nanocapsule surface. In addition, non‐covalent attachments such as biotin‐streptaviding binding, adamantane‐cyclodextrin inclusion and nitrilotiriacetic acid (NTA) metal complexations are also useful functionalization tools for producing smart nanocapsules.…”
Section: Nanocapsules With Controlled Release Propertiesmentioning
confidence: 99%
“…Adamantane functional polymersomes with PDIEM crosslinker units were also reported. Since the corresponding functionalities placed at both inner and outer region of the bilayer membrane as proposed by self‐assembly principles, the post‐conjugation with cyclodextrin modified glycodendrimers was shown by tuning the membrane permeability as open and closed states through the trigger of pH‐stimulus …”
Section: Nanocapsules With Controlled Release Propertiesmentioning
confidence: 99%